Joint Association of Genome-Wide Association Study–Identified Susceptibility Loci and Dietary Patterns in Risk of Renal Cell Carcinoma Among Non-Hispanic Whites. Issue 5 (22nd July 2014) - Melkonian, Stephanie C.; Daniel, Carrie R.; Hildebrandt, Michelle A. T.; Tannir, Nizar M.; Ye, Yuanqing; Chow, Wong-Ho; Wood, Christopher G.; Wu, Xifeng
Abstract : Dietary factors may affect risk of renal cell carcinoma (RCC). In an ongoing case-control study of RCC initiated in Houston, Texas, in 2002, we identified 3 empirically derived dietary patterns: "fruits and vegetables, " "American/Western, " and "Tex-Mex." Among 659 RCC cases and 699 controls, we evaluated associations of these dietary patterns with RCC risk and whether the associations varied by obesity status, smoking status, physical activity level, history of hypertension, and genetic variants previously identified via genome-wide association studies. Among persons in the highest categories of adherence versus the lowest, the "fruits and vegetables" dietary pattern was associated with an approximately 50% lower RCC risk ( P trend < 0.001), while "American/Western" dietary pattern scores were positively associated with a 2-fold higher risk ( P trend < 0.001). We observed synergistic interaction between the American/Western pattern and hypertension status: The odds ratio (highest tertile vs. lowest) among persons with hypertension was 2.23 (95% confidence interval: 1.43, 3.45), as compared with 1.76 (95% confidence interval: 1.16, 2.70) among persons without hypertension (additive P interaction = 0.01). A variant (rs718314) in the inositol 1, 4, 5-trisphosphate receptor, type 2 gene ( ITPR2 ) was found to interact with the American/Western dietary pattern in relation to RCC risk (additive P interaction = 0.03). ITPR2 has been shown to affect nutrient metabolism and central obesity. Dietary patterns, genetic variants, and host characteristics may individually and jointly influence susceptibility to RCC.